(untitled) (Sir Salimullah Medical College Journal, 2022)
Male breast cancer is a rare cancer that forms in the breast tissue of men. Though breast cancer is most commonly thought of as a disease that affects women, it does occurs in men. Male breast cancer is most common in older men, in between ages 60 and 70, though it can rarely occur under age 35. Common predisposing causes that raise odds for male breast cancer includes-breast cancer in a first degree relatives, history of radiation exposure to chest, enlarged breast (gynaecomastia) because of excess endogenous or exogenous estrogens, obesity, mutation of BRCA2 gene (common), cirrhosis of liver, history of some drugs intake, alcoholism, klinefelter’s syndrome, diseases of the testicles such as mumps orchitis or orchidectomy, prostate cancer or may be idiopathic. Here we present a case of older aged man who reported with a lump and itching of the left breast for one year in OPD of a general clinic in Munshigonj. The patient was referred to the unit-1, department of surgery, Sir Salimullah Medical College Mitford Hospital where clinical diagnosis was carcinoma of left breast. Sir Salimullah Med Coll J 2021; 29(2): 166-168